Average correlation as an indicator for nonclassicality - Michael E. N. Tschaffon; Johannes Seiler; Matthias Freyberger (Physical Review Research, 2023)
Bell inequalities are an essential part of quantum information theory. Based on these fundamental inequalities, we propose a different indicator for nonclassicality in the Bell sense: average correlation. We derive a general expression for average correlation and calculate its value for pure states and Werner states. From there we show how two inequalities emerge which serve as necessary and sufficient conditions for nonclassicality. They are simple to evaluate and can even be used to classify all bipartite qubit states.